2015
DOI: 10.1016/j.neuropsychologia.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D4 (DRD4) gene modulates the influence of informational masking on speech recognition

Abstract: Listeners vary substantially in their ability to recognize speech in noisy environments. Here we examined the role of genetic variation on individual differences in speech recognition in various noise backgrounds. Background noise typically varies in the levels of energetic masking (EM) and informational masking (IM) imposed on target speech. Relative to EM, release from IM is hypothesized to place greater demand on executive function to selectively attend to target speech while ignoring competing noises. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 96 publications
(132 reference statements)
2
14
0
Order By: Relevance
“…In addition, demands on working memory likely increase, as listeners probably retain some of the content of the masking signal in working memory and this must subsequently be selectively inhibited at the lexical level ( Tun et al, 2002 ; Van Engen and Bradlow, 2007 ; Cooke et al, 2008 ; Mattys et al, 2009 ; Dekerle et al, 2014 ). Neuropsychological and genetic studies further suggest that populations that are predisposed to show poorer selective attention, as indexed either by increased degree of depressive symptoms ( Chandrasekaran et al, 2015 ) or genetic markers associated with poorer executive function ( Xie et al, 2015 ) experience greater interference in conditions that emphasize informational masking as compared to those involving primarily energetic masking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, demands on working memory likely increase, as listeners probably retain some of the content of the masking signal in working memory and this must subsequently be selectively inhibited at the lexical level ( Tun et al, 2002 ; Van Engen and Bradlow, 2007 ; Cooke et al, 2008 ; Mattys et al, 2009 ; Dekerle et al, 2014 ). Neuropsychological and genetic studies further suggest that populations that are predisposed to show poorer selective attention, as indexed either by increased degree of depressive symptoms ( Chandrasekaran et al, 2015 ) or genetic markers associated with poorer executive function ( Xie et al, 2015 ) experience greater interference in conditions that emphasize informational masking as compared to those involving primarily energetic masking.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, listeners are often required to attend selectively to a talker when there are competing talkers in the background. This well-known "cocktail-party" phenomenon (Cherry, 1953) presents a formidable computational challenge to the brain on a daily basis (Mesgarani & Chang, 2012;Xie, Maddox, Knopik, McGeary, & Chandrasekaran, 2015). Previous studies examining the dynamics of speech-in-speech processing have focused on masker properties, such as similarities in voice features between target and masking talkers (e.g., Brouwer, Van Engen, Calandruccio, & Bradlow, 2012;Brungart, Simpson, Ericson, & Scott, 2001), the impact of increasing the number of masking talkers (e.g., Freyman, Balakrishnan, & Helfer, 2004;Simpson & Cooke, 2005), and the spatial separation of target from masker (e.g., Freyman, Balakrishnan, & Helfer, 2001;Li, Daneman, Qi, & Schneider, 2004).…”
mentioning
confidence: 99%
“…Previous studies examining the dynamics of speech-in-speech processing have focused on masker properties, such as similarities in voice features between target and masking talkers (e.g., Brouwer, Van Engen, Calandruccio, & Bradlow, 2012;Brungart, Simpson, Ericson, & Scott, 2001), the impact of increasing the number of masking talkers (e.g., Freyman, Balakrishnan, & Helfer, 2004;Simpson & Cooke, 2005), and the spatial separation of target from masker (e.g., Freyman, Balakrishnan, & Helfer, 2001;Li, Daneman, Qi, & Schneider, 2004). Recent studies have documented significant individual differences in speech-in-speech processing ability that relate to listener characteristics, such as working memory or neurocognitive profiles, for cocktail-party-like scenarios (e.g., Xie et al, 2015;Zekveld, Rudner, Johnsrude, & Rönnberg, 2013). These studies have collectively indicated that individual differences in cognitive processing may relate to speech processing ability in conditions that require listeners to ignore irrelevant linguistic information in the background (e.g., Anderson, White-Schwoch, Parbery-Clark, & Kraus, 2013;Chandrasekaran, Van Engen, Xie, Beevers, & Maddox, 2015;Xie et al, 2015;Zekveld, Rudner, Johnsrude, & Rönnberg, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that speech recognition thresholds are related to higher cognitive functions, such as working memory and attention (Lunner 2003;Xie et al 2015). Given that patients with ADHD often experience working memory and attention problems, it may be speculated that lower speech recognition thresholds in ADHD are related to deficits in higher cognitive functions.…”
Section: Complex Perception In Adhdmentioning
confidence: 99%